Gen Z Sehat, Gen Z Cerdas: Edukasi Penyakit Menular Seksual untuk Masa Depan Lebih Aman - Fitriani Fitriani; Ridni Husnah; Agnes Jelita Sihol Marito Tampubolon (CV. ALIM'SPUBLISHING, 2026)
The high prevalence of Sexually Transmitted Infections (STIs) and HIV in Batam City represents a serious health issue driven by low adolescent sexual health literacy and persistent social taboos. This community service activity aimed to enhance students' knowledge, awareness, and preventive understanding regarding STIs through adolescent-friendly interactive media approaches. The intervention involved 55 students serving as committee members of the Youth Red Cross (PMR) and Student Council (OSIS) at SMAN 23 Batam. The implementation method combined PowerPoint presentations, educational animated videos, game-based learning simulations, icebreakers, and interactive Q&A sessions. Program success was quantitatively evaluated using a One-Group Pretest-Posttest Design and analyzed via a Paired Samples T-Test. The findings revealed a significant increase in participants' understanding before and after the intervention. The mean knowledge score rose markedly from 52.40 (SD = 11.25) during the pre-test to 88.60 (SD = 8.42) in the post-test, with a p-value < 0.001. The minimum score increased from 30.00 to 70.00, while the maximum score reached a perfect 100.00. The decrease in standard deviation indicated a more homogeneous distribution of knowledge at a higher level of understanding. These findings demonstrate that visual-interactive educational interventions effectively improve reproductive health literacy, overcome psychological barriers, and shift social taboos into scientific understanding that fosters STI prevention behaviors among Generation Z.